2017
DOI: 10.3892/mmr.2017.6109
|View full text |Cite
|
Sign up to set email alerts
|

The metastasis suppressor gene KISS-1 regulates osteosarcoma apoptosis and autophagy processes

Abstract: The expression of the metastasis suppressor gene KISS-1 in osteosarcoma cells during apoptosis and autophagy was evaluated. MG-63 osteosarcoma cells were transfected with either KISS-1 overexpression or KISS-1 knockdown expression vector in vitro, and compared with cell lines transfected with empty vector. After 12, 24, 48 and 72 h of cell culture, the cell proliferation was examined. The MTT method was used to detect apoptosis by flow cytometry, and the mRNA levels of apoptosis and autophagy markers caspase-3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 11 publications
0
8
1
Order By: Relevance
“…Meanwhile, it is significantly related to the time of lung metastasis-free survival (MFS) ( Chen et al, 2019 ). Yin et al (2017) showed that the metastasis inhibitor gene KISS-1 modulated apoptosis and autophagy processes of osteosarcoma. However, the molecular mechanism of CDCA4 in osteosarcoma has not been clarified.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, it is significantly related to the time of lung metastasis-free survival (MFS) ( Chen et al, 2019 ). Yin et al (2017) showed that the metastasis inhibitor gene KISS-1 modulated apoptosis and autophagy processes of osteosarcoma. However, the molecular mechanism of CDCA4 in osteosarcoma has not been clarified.…”
Section: Discussionmentioning
confidence: 99%
“…By down-regulating Gαq-p63RhoGEF-RhoA signaling pathways, Cho et al (16) found that the KISS1 receptor GPR54 gene could delay the development of breast cancer. Recently, Yin et al (17) reported that KISS1 inhibited the proliferation of OS in vitro by accelerating the processes of apoptosis and autophagy in the cells. Conversely, the high expression of KISS1/GPR54 showed poor prognosis in several other kinds of malignant tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, KiSS-1 overexpression has been documented to regulate apoptosis by increasing caspase 3 and Bax and decreasing Bcl-2 and Bax mRNA levels in human osteosarcoma MG-62 and U2OS cells. In these cell lines, KiSS-1 overexpression reduces the extent of both cell proliferation and invasiveness ( 45 ).…”
Section: Kiss-1 As a Metastasis Suppressor Genementioning
confidence: 99%